Peningkatan Produksi dalam Sistem Ekonomi Islam sebagai Upaya Pemberdayaan Ekonomi Umat - Gufron, Moh Idril (Universitas Trunojoyo Madura, 2015)
Abstract The main cause of the emergence of economics and the reason why people need it is the condition that the needs of people are unlimited while the resources to meet them are limited. Dealing with this, economics offers two main things as its orientation, which are choosing and creating process. Choosing process relates to consumption and distribution activities, while creating is all about the process of production or creating a new product. Therefore, those three activities, production, distribution and consumption, play very important role in coping with economic problems.In its universal and comprehensive teachings, Islam also examines how those three practices, production, distribution and consumption should be properly conducted. However, in this article, I will only explain about how Islamic perspective on the increase of production as an effort in empowering people or ummat’s economy is.Islamic economy empowerment could be conducted by raising income as a result of the production increase in the sector of useful goods through the utilization of resources (natural and human resources, capital and organization) at its maximum level. The process of resource utilization should be conducted according to moral and ethical values. Meanwhile, the improvement of production system on the perspective of Islam does not only mean the increase of income monetarily, but also the improvement of fulfillment of people’s need using minimum effort while still paying attention to Islamic rules about consumption. Additionally, improving production could also be conducted by optimizing various sources or driving factors of people production which possibly work well in increasing people economic level at general such as zakat, tax, bait al mal wa al tamwil, shariah bank etc. Keywords: production, empowerment, people economy. AbstrakPenyebab yang paling mendasar kenapa ilmu ekonomi muncul dan dibutuhkan oleh manusia, yaitu karena kebutuhan manusia yang tidak terbatas sementara sumber daya untuk memenuhi kebutuhan itu terbatas. Untuk mengatasi hal itu, ada dua hal pokok yang menjadi orientasi ilmu ekonomi, yaitu memilih dan menciptakan. Memilih berkaitan dengan konsumsi dan distribusi, dan menciptakan berkaitan dengan produksi.Dengan demikian, ketiga aktivitas tersebut (produksi, distribusi, dan konsumsi) memiliki peranan yang sangat penting dalam menyelesaikan persoalan ekonomi.Islam dalam ajarannya yang universal dan komprehensif juga membahas tentang bagaimana produksi, distribusi dan konsumsi seharusnya dilakukan. Namun di dalam artikel ini, penulis hanya menjelaskan tentang bagaimana pandangan islam terhadap peningkatan produksi sebagai upaya pemberdayaan ekonomi umat.Pemberdayaan ekonomi umat dalam Islam dapat dilakukan dengan menaikkan pendapatan sebagai akibat meningkatnya produksi dari barang-barang yang berfaedah melalui pemanfaatan sumber-sumber daya (tenaga alam, tenaga manusia, modal, dan organisasi) secara maksimum. Proses pemanfaat sumber daya tersebut harus dilakukan dengan tetap berpegang pada nilai-nilai moral dan etika. Perbaikan sistem produksi dalam Islam tidak hanya berarti meningkatnya pendapatan yang diukur dari segi uang, tetapi juga perbaikan dalam memaksimalkan terpenuhinya kebutuhan dengan usaha minimal tetapi tetap memperhatikan tuntutan Islam tentang konsumsi. Selain itu, meningkatkan produksi juga dilakukan dengan mengoptimalkan sumber-sumber atau penggerak produksi umat yang bisa meningkatkan ekonomi masyarakat banyak, seperti zakat, pajak, bait al-mal wa al-tamwil, bank syari’ah dan lain sebagainya.Keywords : Produksi, pemberdayaan, ekonomi umat.